The Reproduction of Species: Humans, Animals and Species Nonconformity in Early Rabbinic Science - Neis, Rachel (Jewish studies quarterly, 2017)
Tracing an early rabbinic approach to the human, this article analyzes how the Tannaim of the Mishnah and Tosefta set the human side by side with other species, and embedded their account within broader considerations of reproduction, zoology and species crossings. The human here emerges at the intersection of menstrual purity law and Temple sacrificial law in the tractates of Niddah and Bekhorot and is part of a reproductive biology that sought to determine the boundaries and overlaps between species. This rabbinic biology ought to be understood amid ancient conversations about what constitutes a proper member of a species, in terms of reproduction, resemblance and variation. The article shows how, even as it disavows genealogical links between humans and animals (and indeed across other species), rabbinic reproductive biology nonetheless implicates humans among and as animals.